The effect of exercise using resistance bands on improving the balance of badminton athletes - FransFile Manihuruk; Sumaryanto Sumaryanto; Sigit Nugroho; Sumarjo Sumarjo; Ahmad Nasrulloh; Setyawan Widyarto (Faculty of Sports Sciences, Universitas Negeri Yogyakarta, 2023)
The game of badminton required good physical condition such as balance. This study aims to determine the effect of training using resistance bands on improving the balance of badminton athletes. The benefits of this study, 1) theoretically this research opens the paradigm in the field of coaching in general and specifically in the sport of badminton to use varied forms of exercise, 2) this research is expected to increase knowledge to trainers so that they choose a form of exercise that is simple but can improve various physical conditions, 3) as a reference value for the quality of further research because this research from the knowledge of researchers has not been carried out. This study uses an experimental method with a one group pretest-postest research design. The population in this study were 20 badminton athletes PB.PT.One. The sample in this study were 20 badminton athletes PB.PT.One with total sampling. Data collection techniques are carried out measuring balance with a strok stand measuring instrument. The data analysis technique used is using SPSS 26 software to test the Independent T-Test. The results showed that there was an increase from training using resistance bands to improving the balance of badminton athletes with a value of 0.00 0.05 and an increase from the treatment given of 63%. Training using resistance bands is the right alternative choice to improve physical condition abilities, and which includes balance. It can be an alternative for athletes or badminton coaches to use resistance bands as a medium and method to improve balance.